Índice de formalidad laboral y su influencia en la brecha de género en ingresos laborales en regiones amazónicas del Perú periodo 2018-2024 - Oliveira Sanchez, Ashly Scarlett (2025)
The study examined the influence between the labor formality index and the gender gap in labor income in the Amazonian regions of Peru during the period 2018-2024, finding that there is no statistically significant association between both variables, the results show that variations in the level of labor formality do not have a relevant effect on the reduction or widening of wage differences between men and women, this pattern was maintained both at the aggregate level and in the analysis for each region, evidencing that wage inequalities respond to deeper structural and sectoral factors, such as male concentration in better-paid activities, occupational segregation and the limited application of labor policies with a gender approach, in the descriptive analysis, it was observed that the levels of labor formality in the Amazonian regions have remained low and below the national average, with significant falls in some periods and partial recoveries that fail to reverse accumulated losses. Likewise, the gender gap in labor income has shown unstable behavior, with temporary reductions followed by increases, especially in recent years, reflecting the fragility of progress in wage equity. These findings suggest that closing the gender gap is not enough to promote employment formalization; rather, it is necessary to implement comprehensive strategies that combine productive diversification, the inclusion of women in the labor force in strategic sectors, and the strengthening of equal pay policies with effective oversight and monitoring mechanisms.